Quantitative trait loci mapping and gene network analysis implicate protocadherin‐15 as a determinant of brain serotonin transporter expression. (6th February 2014) - Ye, R.; Carneiro, A. M. D.; Han, Q.; Airey, D.; Sanders‐Bush, E.; Zhang, B.; Lu, L.; Williams, R.; Blakely, R. D.
<x xml:space="preserve">Abstract</x> Presynaptic serotonin (5‐hydroxytryptamine, 5‐HT) transporters (SERT) regulate 5‐HT signaling via antidepressant‐sensitive clearance of released neurotransmitter. Polymorphisms in the human SERT gene (SLC6A4) have been linked to risk for multiple neuropsychiatric disorders, including depression, obsessive‐compulsive disorder and autism. Using BXD recombinant inbred mice, a genetic reference population that can support the discovery of novel determinants of complex traits, merging collective trait assessments with bioinformatics approaches, we examine phenotypic and molecular networks associated with SERT gene and protein expression. Correlational analyses revealed a network of genes that significantly associated with SERT mRNA levels. We quantified SERT protein expression levels and identified region‐ and gender‐specific quantitative trait loci (QTLs), one of which associated with male midbrain SERT protein expression, centered on the protocadherin‐15 gene (Pcdh15), overlapped with a QTL for midbrain 5‐HT levels. Pcdh15 was also the only QTL‐associated gene whose midbrain mRNA expression significantly associated with both SERT protein and 5‐HT traits, suggesting an unrecognized role of the cell adhesion protein in the development or function of 5‐HT neurons. To test this hypothesis, we assessed SERT protein and 5‐HT traits in the Pcdh15 functional null line (Pcdh15av‐3J), studies that revealed a strong, negative influence of Pcdh15 on these phenotypes. Together, our findings illustrate the power of multidimensional profiling of recombinant inbred lines in the analysis of molecular networks that support synaptic signaling, and that, as in the case of Pcdh15, can reveal novel relationships that may underlie risk for mental illness.